Assessing Hydrolyzed Gluten Content in Dietary Enzyme Supplements Following Fermentation - Ekaterina Khokhlova; Pyeongsug Kim; Joan Colom; Shaila Bhat; Aoife M. Curran; Najla Jouini; Kieran Rea; Christopher Phipps; John Deaton (Fermentation, 2022)
Partially digested gluten fragments from grains including wheat, rye, spelt and barley are responsible for triggering an inflammatory response in the intestinal tract of Celiac Disease (CD) and Non-Celiac Gluten Sensitive (NCGS) individuals. Fermentation is an effective method to metabolize gluten, with enzymes from bacterial or fungal species being released to help in this process. However, the levels of gluten in commercially available enzymes, including those involved in gluten fermentation, are unknown. In this study we investigated gluten levels in commercially available dietary enzymes combined with assessing their effect on inflammatory response in human cell culture assays. Using antibodies that recognize different gluten epitopes (G12, R5, 2D4, MloBS and Skerritt), we employed ELISA and immunoblotting methodologies to determine gluten content in crude gluten, crude gliadin, pepsin-trypsin digested gluten and a selection of commercially available enzymes. We further investigated the effect of these compounds on inflammatory response in immortalized immune and intestinal human cell lines, as well as in peripheral blood mononuclear cells (PBMCs) from coeliac individuals. All tested supplemental enzyme products reported a gluten concentration that was equivalent to or below 20 parts per million (ppm) as compared with an intact wheat reference standard and a pepsin-trypsin digested standard. Similarly, the inflammatory response to IL-8 and TNF-α inflammatory cytokines in mammalian cell lines and PBMCs from coeliac individuals to the commercial enzymes was not significantly different to 20 ppm of crude gluten, crude gliadin or pepsin-trypsin digested gluten. This combined approach provides insight into the extent of gluten breakdown in the fermentation process and the safety of these products to gluten-sensitive individuals.